Effect of HVOF spraying parameters on fracture, erosion and thermal properties of Fe alloy-based coating materials. (July 2021) - Sharma, Ratnesh Kumar; Das, Randip Kumar; Kumar, Shiv Ranjan
Fe-based coating (Fe50Mo5C15Si10Cr10Ti10) was deposited on 316L stainless steel substrate by high-velocity oxy-fuel spraying coating process. High-velocity oxy-fuel spraying process parameters such as oxygen flow rate and spray distance were varied to investigate their effect on mechanical, wear and thermal properties. The prepared coatings were characterized in terms of mechanical properties such as micro-hardness and fracture toughness, thermal properties and erosion wear properties. X-ray diffraction analysis showed presence of hardened phase Fe2 Ti and Fe-Cr. Results of this study indicated that increase in oxygen flow rate from 200 to 250 slpm improved the fracture toughness and micro-hardness by 33% and 6.7%, respectively. On the other hand, increase in spray distance decreased the fracture toughness and micro-hardness by 27.2% and 6.7%, respectively. The wear rate was increased with the increase in oxygen flow rate and decreased with the increase in spray distance. The erosion wear rate was more dependent on fracture toughness as compared to micro-hardness.